'Due to all this fear, we're getting less freedom': young people's understandings of gender and sexual violence in New Delhi, India. Issue 2 (17th February 2019) - Iyer, Padmini
ABSTRACT: This paper explores young people's understandings of gender and sexual violence in New Delhi, India, based on multi-method research conducted with young people (aged 15–17) in three co-educational secondary schools. Fieldwork took place shortly after the 2012 Delhi gang rape that sparked widespread debates about violence against women in India, and so sexual violence became an important frame for students' discussions around gender and sexuality. Young people's understandings are considered within gender narratives – of 'can-do' and 'vulnerable' girlhood, and of 'hero' and 'good boy' masculinities – which already shaped their day-to-day experiences of schooling. Findings suggest that tensions arising from these often contradictory narratives led to frustrations among girls, while the dominance of conversations about sexual violence led to confusions in both girls' and boys' understandings of sexuality. Reflections are offered on ways schools can better support young people as they learn about gender and sexuality from diverse and contradictory sources.